Pengaruh Terpaan Informasi Kemasan Rokok terhadap Minat Merokok Pelajar - Pratama, Aditya (Jurnal The Messenger, 2016)
This study aimed to determine the effect of exposure to information from the packaging cigarette packs, the interest on student smoking. The cornerstone of the theory used in this research is adopted from Morrison, et al (2010) which states that the attitude change theory provides an explanation of how a person's attitude is formed. The research method is by questionnaires and questionnaires using purely experimental methods. The study population was Students - Students of class X SMA Negeri 2 Semarang, whereas samples taken were 32 students. It was concluded that there is a strong influence of the variable Wrap Cigarette Packaging Information Exposure to smoke on student interest. It is based on research results that showed a significance level of 0.000 <0.05, which means that the more often the frequency of affected teens notice or information on the packaging of the cigarette pack, the lower the interest teenagers to smoke.